Unsteady MHD Flow Due to Non-Coaxial Rotations of a Porous Disk and a Fluid at Infinity Subjected to a Periodic Suction - M. Guria (International Journal of Applied Mechanics and Engineering, 2018)
The unsteady flow of a viscous incompressible electrically conducting fluid due to non-coaxial rotations of a porous disk subjected to a periodic suction and the fluid at infinity in the presence of applied transverse magnetic field has been studied. The fluid at infinity passes through a fixed point. The velocity field, shear stresses are obtained in a closed form.